Surface Al and Co coordination for peroxymonosulfate activation: identification and mechanism - Zhu, Min-Ping (2023)
Deciphering the metal-support interaction-oriented catalysis on millimeter-scaled catalysts is highly desirable yet remains scarce in Fenton-like catalysis. Herein, we fine-tune the support-surface reconstruction of Co2AlO4 on γ-Al2O3 millispheres and reveal the origins of its activity in peroxymonosulfate activation by nuclear magnetic resonance and X-ray photoelectron/adsorption spectroscopy. Calcination of γ-Al2O3 supports rearranged their surface octahedral, tetrahedral and pentacoordinate Al3+. The reconstructed tetrahedral and pentacoordinate Al3+ as binding sites regulated the formation of Co2AlO4 with coordinated Co3+/Co2+ redox centers via strong metal-support interactions. The activities of tailored Co2AlO4 @Al2O3 millispheres in activating peroxymonosulfate follow different binomial models, highly relying on their Co3+/Co2+ ratio, contents of lattice O and pentacoordinate Al3+. The Co-O-Al bonds endow the millimeter-scaled Co2AlO4 @Al2O3 with robust catalytic activity, stability and reusability. The exposed Co2AlO4 (200) surface is responsible for the decomposition of PMS into produce SO4•[sbnd] and 1O2 as the dominant oxidants for water detoxification.